What soft skills do Tanzania employers prefer among graduates in the world of work? - Mayega, Jovitha Lazaro (Papers in Education and Development, 2024)
This study investigated the soft skills preferred by Tanzanian employers among graduates in the world of work. It specifically explored employers’ perspectives on the top five soft skills graduates should possess. A qualitative research approach with a descriptive phenomenological design was employed. Six employers were purposively selected, and data were collected through semi-structured interviews and document reviews, then analysed thematically. The study's findings indicated that employers value graduates who are self-aware of workplace dynamics, effective in communication, uphold integrity, demonstrate independence, and possess problem-solving skills. These soft skills enhance graduates’ employability, especially in organisations with blended and diverse cultures. The findings underscore the importance of graduates demonstrating soft skills in the workplace. The study recommends educational interventions to address soft skills mismatches and support graduates in securing both public and self-employment. Further research should explore effective teaching and learning approaches for enhancing soft skills among students.